2008
DOI: 10.3176/proc.2008.4.07
|View full text |Cite
|
Sign up to set email alerts
|

Single-subunit allostery in the kinetics of peptide phosphorylation by protein kinase A

Abstract: Allosteric cooperativity between peptide and ATP binding sites on cAMP-dependent protein kinase catalytic subunit was studied kinetically for the reaction of phosphorylation of seven peptide substrates. The allosteric effect was quantified in terms of the interaction factor α by comparing binding effectiveness of a substrate molecule with the free enzyme and with the enzyme complex with another substrate. It was discovered that the magnitude of the allosteric feedback between these binding sites was governed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Our recent kinetic studies have revealed that the catalytic activity of protein kinase A was indeed governed by interaction between binding sites of two different substrates which can be said to be allosteric [10,11]. Moreover, allosterically regulated ligand binding properties have been observed for this enzyme also in several ligand binding studies, as summarized below.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Our recent kinetic studies have revealed that the catalytic activity of protein kinase A was indeed governed by interaction between binding sites of two different substrates which can be said to be allosteric [10,11]. Moreover, allosterically regulated ligand binding properties have been observed for this enzyme also in several ligand binding studies, as summarized below.…”
Section: Introductionmentioning
confidence: 98%
“…4, as initially mentioned in our previous paper [10]. These data were characterized by the intercept value C b = -1.4 ± 0.1 and by the slope value S b = 0.43 ± 0.03.…”
Section: Linear Free-energy Relationships and Allosterymentioning
confidence: 99%
See 3 more Smart Citations